2021
DOI: 10.3390/mi12020157
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Flexible Electronics: Set Device Lifetime with Smart Nanomaterials

Abstract: Flexible electronics is one of the most attractive and anticipated markets in the internet-of-things era, covering a broad range of practical and industrial applications from displays and energy harvesting to health care devices. The mechanical flexibility, combined with high performance electronics, and integrated on a soft substrate offer unprecedented functionality for biomedical applications. This paper presents a brief snapshot on the materials of choice for niche flexible bio-implanted devices that addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…We can find them in almost anything of quotidian use, from simple things such as cell phone charges [ 1 ] to TVs and home appliances. However, they have become more relevant in the development of electric and hybrid vehicles, electric machines [ 2 ], renewable energy systems [ 3 , 4 , 5 , 6 ], and recently in implanted electronics [ 7 , 8 ] to open the possibility to micro-scale neural interfaces [ 9 ]. Inside these devices and systems, a power stage is conformed by magnetic and electronic components.…”
Section: Introductionmentioning
confidence: 99%
“…We can find them in almost anything of quotidian use, from simple things such as cell phone charges [ 1 ] to TVs and home appliances. However, they have become more relevant in the development of electric and hybrid vehicles, electric machines [ 2 ], renewable energy systems [ 3 , 4 , 5 , 6 ], and recently in implanted electronics [ 7 , 8 ] to open the possibility to micro-scale neural interfaces [ 9 ]. Inside these devices and systems, a power stage is conformed by magnetic and electronic components.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 summarizes material properties of frequently-used diffusion barrier of the biocompatible package. Diffusion barrier is a dielectric film deposited on a Si surface or an encapsulating polymer to avoid liquid passage through biocompatible package [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The dielectric layer, Al 2 O 3 deposited by ALD (Atomic Layer Deposition) is frequently used as moisture barrier between polymer layers to increase adhesion strength between the polymer layers or enhance the life-time of a neural electrode bilayered with parylene material [ 41 , 42 ].…”
Section: Biocompatible Packaging Methodsmentioning
confidence: 99%
“…For submicron LM particles, the rupture stress versus diameter relationship has been determined. 66 They found that the activation stress was inversely proportional to the diameter of the LM droplets, meaning larger droplets ruptured with less stress, calculated as shown in Equation (1).…”
Section: Activation Of Liquid Metal Inclusionsmentioning
confidence: 99%
“…In recent years, the adoption rate of wearable electronics has begun to surge from its prototypical infancy in the early part of the last decade. The demand for such devices is driven by, but not limited to, the increasing desire for continuous health monitoring, [1][2][3][4] controlled delivery of nanomedicines, [5][6][7] advancement of soft robotics, [8][9][10][11][12] and physically immersive virtual/augmented reality products. [13][14][15] A limitation that these diverse technologies all have in common is the constraints set by current rigid electronics that force their soft environments to conform around them.…”
Section: Introductionmentioning
confidence: 99%